Climatic potential for summer and winter wine production - de Oliveira Aparecido, Lucas Eduardo [UNESP]; Moreto, Victor Brunini [UNESP]; de Souza Rolim, Glauco [UNESP]; da Silva Cabral de Moraes, José Reinaldo [UNESP]; Valeriano, Taynara Tuany Borges [UNESP]; de Souza, Paulo Sergio [UNESP] (Wiley, 2018)
BACKGROUND: The geoviticultural multicriteria climatic classification (MCC) system provides an efficient guide for assessing the influence of climate on wine varieties. Paraná is one of the three states in southern Brazil that has great potential for the expansion of wine production, mainly due to the conditions that favour two harvests a year. The objective was to apply the geoviticultural MCC system in two production seasons. We used maximum, mean and minimum air temperature and precipitation for 1990–2015 for the state of Paraná. Air temperature and Precipitation were used to calculate the evapotranspiration and water balance. We applied the MCC system to identify potential areas for grapevine production for harvests in both summer and winter and then determined the climatic zones for each geoviticultural climate. RESULTS: Paraná has viticultural climates with conditions favourable for grapevine cultivation for the production of fine wines from summer and winter harvests. The conditions for the winter harvest provided wines with good coloration and high aromatic potential relative to the summer harvest. CONCLUSION: Chardonnay, Merlot, Pinot Blanc and Müller-Thurgau were suitable for regions with lower air temperatures and water deficits. Pinot Blanc and Müller-Thurgau were typical for the southern region of Paraná. © 2017 Society of Chemical Industry.
Keywords: climate; MCC system; modelling; viticultural zoning